Arā’u Ibni Jinnī fī al Ẓawāhiri al Ṣautiyati fī Mīzāni al Dirāsati al Ṣautiati al Mu’āṣirati - Kuswardono, Singgih (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2019)
ABSTRACT IbnJinniy (322-392 A.H./ 933-1001 A.D.) is a well-known language philosopher. He is considered to be the first linguist who defined language as a sound, a sound that is used by community to express their social objectives. No one among linguists has opposed to this definition and it has even been followed by all Arab linguists up to now. IbnJinniy paid attention to speech sound much greater than any linguists in his era and he is regarded to be the first linguist who studied Arabic speech sounds in his work (سر الصناعة) and some others in his book (الخصائص). Whith in IbnJinniy’s views, he had laid down foundation of speech sounds phenomenon more comprehensive than who ever was before him in the past. He became the founder of thoughst and theories in speech sounds phenomenon which linguists make it reference to the present time. According to IbnJinniy, the speech sounds phenomenon consisting: 1) morphophenemic phenomenon; 2) pronunciation phenomenon; 3) metric/ prosodi phenomenon; and 4) dialect phenomenon. Along with linguistic branching out more than 2000 years, the speech sound phenomenon thoughts also grow up. There are some new terms never known before appear, some are similiar as Ibn Jinniys terms, some others improve Ibn Jinniys thought in speech sound phenomenon. Speech sound phenomenon terms which are equal or as same as Ibn Jinny meaning such (المماثلة التامة) equal to (الإدغام الأكبر), (المخالفة) equal to (الإبدال كراهية التضعيف). Whereas some speech sound phenomenon terms which improve or detail Ibn Jinniy thought are: (1) (التخفيف بإزالة التضعيف وفك الإدغام) is the exeptional of (الإدغام الأكبر) for example: (اقتتل واشتتم), (الحمد لله العلي الأجلل); (2) (تخفيف صوت المفرد) is the mutation part of /ا/ on /ء/, such its examples were mentioned by Ibn Jinniy: (آمن) from (أأمن), (راس) from (رأس), and (باس) from (بأس); and (3) (توافق الصوائت) is the explanation about first pronoun form and its changed form, such (عليهِمْ، إليهِم، بِهِ، بِهِمْ) form (عَلَيْهُمْ، إِلَيْهُمْ، بِهُ، بِهُمْ).